Образ поляків і Польщі в українських шкільних підручниках - Батуріна, С. (Сiверянський літопис, 2020)
Мета статті – шляхом аналізу сучасних шкільних підручників реконструювати формування образу взаємин між українцями та поляками впродовж тривалого періоду від середньовіччя до середини ХХ ст. До основних завдань публікації
належить: відслідковування змін, які відбулися (чи не відбулися) у сприйнятті
найближчого сусіда та відносин із ним, у порівнянні з попереднім поколінням
українських підручників; яким чином у них представлені поляки, польська держава та спільне минуле від часів середньовіччя до сьогодення. Методологічною основою публікації є деконструкція текстів українських шкільних підручників для
5–11 кл. Наукова новизна полягає в здійсненому вперше комплексному аналізі такого об'єму текстів підручників у визначеному контексті. Висновки. Відзначено, що поляки і Польща в текстах підручників з'являються в певні історичні періоди,
висвітлення кожного з яких відзначено особливостями, зумовленими економічними, політичними й суспільними чинниками: доба середньовіччя – династичні контакти й мілітарні конфлікти польських королів і руських князів; XIV – перша
половина XVIІ cт. – річпосполитський період від підпорядкування Польщею території Галицько-Волинського князівства і колишніх теренів Русі до Хмельниччини; кінець XVIII–XIX ст. – від Коліївщини до відновлення польської держави;
період ХХ ст. Спільним для висвітлення усіх цих періодів, попри специфіку та
унікальність, є наявність конфлікту. Історія Польщі та україно-польських взаємин актуалізується в підручниках майже винятково через конфронтацію між обома народами в політичній чи військовій площині. The purpose of the article is to analyze the formation of the image of relations
between Ukrainians and Poles during the long period from the Middle Ages to the
middle of the twentieth century by analyzing modern school textbooks. Among the main
objectives of the publication is to track changes that have (or have not) occurred in the
perception and relationship of the nearest neighbor, compared to the previous generation
of Ukrainian textbooks. How do they represent the Poles, the Polish state and the
common past from the Middle Ages to the present? The methodological basis of the
publication is the deconstruction of the texts of Ukrainian school textbooks for grades
5–11. The scientific novelty lies in the first comprehensive analysis of such a volume
of textbook texts in a given context. Conclusions. Poles and Poland appear in the textbooks
during certain historical periods, each of which is highlighted in the textbooks
by specific economic, political and social factors: the Middle Ages – dynastic contacts
and militaristic conflicts between the Polish kings and Russians; 14th – first half of
16th centuries – the Commonwealth period from the subordination by Poland the territory
of the Galicia-Volyn principality and the former territories of Russia to Khmelnytskyi
war; the end of 18th–19th centuries – from the Koliivshchyna to the restoration
of the Polish state; period of the 20th century. Common feature for all these periods,
despite the specifics and uniqueness, is the existence of conflict. The history of Poland
and the Ukrainian-Polish relationship is actualized in textbooks almost exclusively because
of a confrontation between the two nations in the political or military aspects.
In most of the textbooks Poles, as representatives of the ethnic group are represented
to a very small extent. They are replaced by the image of Poland as a state, and the
relations of Ukrainians with the Poles are considered only through the prism of state or
political. The Poles, as representatives of the ethnic group, appear in the texts, except in
statistics, illustrating the national composition of the Ukrainian territories geographically
and chronologically. Compared to the previous generation of Ukrainian school
textbooks, in modern editions old Soviet categories and ethnocentric connotations are
not so explicit. Authors attempt to find compromises, identify the root causes of confl
icts, avoid their unilateral characterization, and make no alternative assessments.